Genetic characterisation of colophospermum mopane (sensu lato) using RAPD analyses - Legodi, Mankone Priscilla (University of Limpopo (Turfloop Campus), 2007)
Colophospermum mopane (sensu lato) is currently recognised on morphological and physiological characteristics. To add to the suite of taxonomic characters, the genetic variability of C. mopane (sensu lato) was investigated using the RAPD technique. DNA was extracted from young seedlings and mature leaves using the CTAB method. Initially, the DNA extraction was problematic due to the presence of polysaccharides, making PCR nearly impossible. An additional phenol precipitation step was introduced to purify the DNA used to perform RAPD analyses. Twenty random primers were tested for their suitability and reproducibility to reveal polymorphism in C. mopane (sensu lato). Nine of the primers tested amplified the genomic DNA. Subsequently, three primers (OPA 03, OPA 08 and OPA 09) were selected based on their reproducibility and demonstration of polymorphism. OPA 03 amplified most of the samples tested whereas OPA 08 and OPA 09 amplified 50% of the samples. RAPD bands ranged from 180 bp to 2000 bp. RAPD profiles of C. mopane (sensu lato) with three random primers showed few polymorphisms. Individual trees of different ecotypes show similar RAPD banding pattern, instances were found where trees of the same ecotype showed different bands. The total character difference based on presence and absence of bands revealed both variability and similarity of C. mopane (sensu lato). Phylogenetic trees from individual primers and combined primers were constructed using Neighbour Joining and Parsimony analysis. The phylogenetic tree from the combined primers of bootstrap parsimony generated three clades with low and high parsimony bootstrap values. The first clade receives weak support (61%) while the second and third clades receive support of 90% and 70%, respectively. The other remaining entities collapsed resulting in basal polytomy. The third clade shows some members of Alba (Alba 11 Phala, Alba 1 Phala and Alba 7 Musina) grouped together. The overall results of C. mopane (sensu lato) show high (84.1%) genetic similarity. No ecotypic marker was obtained. Most of the ecotypes have not diverged genetically far from one another or from the parental material (Mopane – sensu stricto). The genetic results partially support the perceived morphological differences. In this study the RAPD technique has established its value as an additional tool to express the genetic variability in C. mopane (sensu lato).
Thesis (M.Sc. (Molecular and Life Sciences)) --University of Limpopo, 2007
Keywords: Colophospermum mopane; Mopane tree RAPD analyses; 582.16785; Mopane tree; Colophospermum